Solitons in magneto–optic waveguides with Kudryashov's law of refractive index. (November 2020) - Zayed, Elsayed M.E.; Alngar, Mohamed E.M.; Biswas, Anjan; Asma, Mir; Ekici, Mehmet; Alzahrani, Abdullah Kamis; Belic, Milivoj R.
Highlights: Soliton solutions to magneto–optic waveguides are secured. Kudryashov's law of refractive index is considered. Extended auxiliary equation approach is implemented. Solutions in terms of Jacobi's elliptic functions are obtained. Bright, dark and singular soliton solutions are revealed. Abstract: This work employed extended auxiliary equation approach to secure soliton solutions to magneto–optic waveguides that maintains Kudryashov's law of refractive index. First, solutions in terms of Jacobi's elliptic functions are obtained and subsequently upon carrying out the limiting operations when the modulus of ellipticity approaches zero or unity, bright, dark or singular soliton solutions are revealed.